1998
DOI: 10.1128/jcm.36.5.1378-1381.1998
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter Comparison of ESP Culture System II with BACTEC 460TB and with Lowenstein-Jensen Medium for Recovery of Mycobacteria from Different Clinical Specimens, Including Blood

Abstract: The recently developed ESP Culture System II (AccuMed, Chicago, Ill.) was compared with radiometric BACTEC 460TB (Becton Dickinson, Towson, Md.) and with Lowenstein-Jensen medium for recovery of mycobacteria from over 2,500 clinical specimens both of respiratory and nonrespiratory origin, including blood. The majority of the 219 mycobacterial isolates (129) belonged to the Mycobacterium tuberculosis complex, followed by 37 isolates of theMycobacterium avium complex (MAC) and 53 isolates of eight other mycobact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
26
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(29 citation statements)
references
References 14 publications
(12 reference statements)
2
26
1
Order By: Relevance
“…We found that the rate of contamination with the 7-ml Bactec MGIT 960 was lower than the values reported previously for other walk-away broth-based systems (1,2,9,10,11) but was in line with the rates of contamination observed with the 4-ml MGIT (4,5,8). However, the concentration of NaOH used in the other walk-away system studies was lower (2%) than that used both in the present study (4%) and in the 4-ml MGIT studies (3%) (1,2,4,5,8,9,10,11). Moreover, the delay between specimen collection and processing due to longer specimen shipment times at some sites (i.e., 2 to 5 days at one of the test sites in the study by Hanna et al) and the different patient population may also explain these discrepancies (2,4).…”
supporting
confidence: 82%
See 2 more Smart Citations
“…We found that the rate of contamination with the 7-ml Bactec MGIT 960 was lower than the values reported previously for other walk-away broth-based systems (1,2,9,10,11) but was in line with the rates of contamination observed with the 4-ml MGIT (4,5,8). However, the concentration of NaOH used in the other walk-away system studies was lower (2%) than that used both in the present study (4%) and in the 4-ml MGIT studies (3%) (1,2,4,5,8,9,10,11). Moreover, the delay between specimen collection and processing due to longer specimen shipment times at some sites (i.e., 2 to 5 days at one of the test sites in the study by Hanna et al) and the different patient population may also explain these discrepancies (2,4).…”
supporting
confidence: 82%
“…In the present study, the automated 7-ml BACTEC MGIT 960 system displayed a rate of recovery (96.4%) of M. tuberculosis higher than those previously reported for the manual 4-ml MGIT, i.e., 89.4% by Pfyffer et al (4), 81.3% by Somoskövi and Magyar (8), and 85% by Piersimoni et al (5), and also higher than those previously reported for the same walk-away system, i.e., 77% by Hanna et al (2) and 88% by Tortoli et al (10). The 7-ml BACTEC MGIT 960 was also more efficient than the similarly fully automated ESP II system (sensitivity, 85.3 and 89%) (9,11) and showed a sensitivity comparable to that of the MB/BacT system (96%) (1).…”
mentioning
confidence: 56%
See 1 more Smart Citation
“…However, this system has limitations, such as the necessity of daily manual loading, the possibility of cross‐contamination due to the invasive reading, manual data management, and the creation of radioactive waste. Novel non‐radiometric systems based on liquid culture have been developed with the aim of avoiding these drawbacks [3–5]. One of them is the BacT/ALERT 3D system [6] (bioMérieux, Durham, NC, USA), which is based on the detection of CO 2 released by actively proliferating mycobacteria into the liquid media.…”
Section: Recovery Of Mycobacteria From 2659 Clinical Routine Specimenmentioning
confidence: 99%
“…Many other studies have demonstrated a higher isolation rate of MGIT as compared to L-J media. [8,9,10] Studies have found out a much lower incidence of non-tuberculous mycobacteria (NTM) in India. A study from CMC Vellore found out M. tuberculosis to be the predominant isolate (96.1%) as compared to only 3.9% NTM.…”
Section: Discussionmentioning
confidence: 99%